LAMP2A regulates the loading of proteins into exosomes - Ferreira, João Vasco (2022)
Exosomes are extracellular vesicles of endosomal origin that are released by practically all cell types across metazoans. Exosomes are active vehicles of intercellular communication and can transfer lipids, RNAs, and proteins between different cells, tissues, or organs. Here, we describe a mechanism whereby proteins containing a KFERQ motif pentapeptide are loaded into a subpopulation of exosomes in a process that is dependent on the membrane protein LAMP2A. Moreover, we demonstrate that this mechanism is independent of the ESCRT machinery but dependent on HSC70, CD63, Alix, Syntenin-1, Rab31, and ceramides. We show that the master regulator of hypoxia HIF1A is loaded into exosomes by this mechanism to transport hypoxia signaling to normoxic cells. In addition, by tagging fluorescent proteins with KFERQ-like sequences, we were able to follow the interorgan transfer of exosomes. Our findings open new avenues for exosome engineering by allowing the loading of bioactive proteins by tagging them with KFERQ-like motifs.